Pengenalan Zahir Accounting untuk Efisiensi dan Efektivitas Pengelolaan Keuangan UMKM di Kota Tasikmalaya - Dewi, Liana; Renggana, Rafliana Mukhtar; Novi, Alya (LPPM Universitas Flores, 2023)
MSMEs are the driving force of the nation's economy. Therefore, the government is very serious about providing protection and a platform for MSME activists. However, the problems often come from within the MSMEs themselves. The problem most often faced is the low understanding of MSME activists in financial management. Currently, financial management can be assisted by Zahir Accounting. MSME activists should follow technological developments in financial management in order to increase business effectiveness and efficiency. Zahir accounting training will be provided to MSMEs in the Tasikmalaya City area. Community service activities are carried out with partners of the Mosque Cleaning Team (TBM). The participants were 9 TBM members who work as MSME activists. The training was carried out for 3 days. On the first day, participants received material and a poll regarding participants' mastery of technology via the Whatsapp Group. On the second day, Zahir Accounting training was carried out face to face in the computer laboratory room on the Mayasari Bakti University campus. On the third day, an evaluation regarding the implementation of the training and participants' interest in using the Zahir Accounting application in their business was carried out. Participants were enthusiastic and really helped if the Zahir accounting application could be applied in their business. Managing MSME finances using the help of Zahir Accounting provides a new perspective in managing business finances while making it easier to manage MSME finances.